Metode Filsafat Perenialisme Terhadap Akhlak Anak Menurut Imam Al-Ghazali - Munthe, Hasanuddin; Rasyid Siregar, Muhammad Fajar; Erdianto, Rudy (Yayasan Rahmat Islamiyah, 2024)
Perennialism is a trend in education that was born in the twentieth century. Perennialism views the current world situation as full of chaos, especially in moral, intellectual and socio-cultural life. Therefore, efforts need to be made to overcome this. Parennialists can look at the Islamic scholar of the Middle Ages, namely Imam Al-Ghazali. He was very instrumental in Islamic religious education, especially in the field of human morals. The research method used was qualitative research, or library research. Requirements for developing children's morals through the philosophy of perennialism. According to Imam Al Ghazali, learning is a mental process that requires concentration, learning must be based on an attitude of humility, learning to exchange opinions must have solid basic knowledge, learning must know the value and purpose of the knowledge being studied, and learning must be done in stages. The aim of learning is to have moral character. The conclusion of this research report is that the concept of Al-Qur'an education according to Imam Al-Ghazali is that the center of education is education of the heart because the heart is the essence of humans. So, the teacher's job is not only to educate the mind but also to guide, direct, improve and purify the heart to get closer to Allah.